BUDIDAYA TANAMAN HIAS UNTUK MENINGKATKAN PENDAPATAN IBU-IBU RUMAH TANGGA GPBI ZEBULON TIANGWANGKANG BATAM - Erni Yanti Natalia; Tiurniari Purba (PUAN INDONESIA, 2021)
One of the ethnic groups in Batam, from the many tribes, is the sea tribe. The inhabitants of the Sea Tribe live along the edge of the coastal line known as "Barelang" (Batam-Rempang-Galang). Barelang is well-known as a destination for foreign and local tourists and has even become an icon of the city of Batam. Kampung Tua Tiangwangkang itself is locate in Barelang. The population of the sea tribe is 63 heads of families with a population of 203 people. The types of professions that the residents are engaged in are fishermen, restaurant employees and manual laborers with daily wages to fulfill their daily needs. Including housewives doing the profession as daily manual labor. To reduce the burden on housewives in Tiangwangkang, the PKM program held training in ornamental plant cultivation with the aim of increasing housewives' income in helping the family economy. This PKM activity was held for two meetings, the first meeting provided training on how to cultivate ornamental plants and in the second meeting taught housewives about online marketing. This activity ran smoothly and had a big impact because each of the participants in the exercise had become proficient in practicing how to grow ornamental plants.